1973
DOI: 10.1073/pnas.70.6.1855
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Activity in Erythrocyte Ghosts of Patients with Myotonic Muscular Dystrophy

Abstract: Myotonic muscular dystrophy is a disorder of humans that involves many organ systems. Physiological studies have suggested that the fundamental defect is of membrane origin. Heretofore, no reproducible metabolic abnormalities have been demonstrated. In the present studies we used erythrocyte ghosts as a convenient source of purified membranes that do not possess changes of denervation, dystrophy, and fibrosis that might complicate the interpretation of muscle membrane changes. Our experiments demonstrated a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

1976
1976
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 36 publications
(28 reference statements)
2
25
0
1
Order By: Relevance
“…This work extends the original observations of Roses and Appel linking DM to membrane protein phosphorylation (13)(14)(15) and reconfirms the role of HMPK as the active agent in DM (5,36,37). Moreover, these findings link the pathophysiology of DM (altered Na channel kinetics to the genetic abnormality) a mutation in a gene whose product has sequence similarity to protein kinases.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This work extends the original observations of Roses and Appel linking DM to membrane protein phosphorylation (13)(14)(15) and reconfirms the role of HMPK as the active agent in DM (5,36,37). Moreover, these findings link the pathophysiology of DM (altered Na channel kinetics to the genetic abnormality) a mutation in a gene whose product has sequence similarity to protein kinases.…”
Section: Discussionsupporting
confidence: 85%
“…This finding substantiates earlier biochemical studies of protein phosphorylation in erythrocytes and muscle isolated from DM patients (13)(14)(15). It has therefore been suggested that HMPK normally regulates ion channel function (16,17).…”
Section: Introductionsupporting
confidence: 89%
“…(c) A reduction of diacylglycerol kinase activity necessary for the conversion of diacylglycerol to phosphatidic acid. Additional experimental data will be necessary to decide among these possibilities as well as to determine the relationship of these data to altered band 3 phosphorylation (2,(4)(5)(6) or the other disturbances in membrane function that have been previously described in this disorder (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by variable penetrance and expression (1). The involvement of multiple organ systems has led to a suspicion that the disease results from a generalized defect in cellular membrane function (2,3). This hypothesis has been supported by observations in muscle from MyD patients indicating a decreased membrane protein phosphorylation associated with no differences in protein content or other membrane marker enzymes (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation